Scientific commentary: Strategic analysis of environmental policy risks-heat maps, risk futures and the character of environmental harm - Prpich, George; Dagonneau, J.; Rocks, Sophie A.; Lickorish, Fiona A.; Pollard, Simon J. T. (Elsevier Science B.V., Amsterdam., 2013)
We summarise our recent efforts on the policy level risk appraisal of environmental risks. These have necessitated working closely with policy teams and a requirement to maintain crisp and accessible messages for policy audiences. Our comparative analysis uses heat maps, supplemented with risk narratives, and employs the multidimensional character of risks to inform debates on the management of current residual risk and future threats. The policy research and ensuing analysis raises core issues about how comparative risk analyses are used by policy audiences, their validation and future developments that are discussed in the commentary below.